2019
DOI: 10.1038/s41598-019-44457-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved TGIRT-seq methods for comprehensive transcriptome profiling with decreased adapter dimer formation and bias correction

Abstract: Thermostable group II intron reverse transcriptases (TGIRTs) with high fidelity and processivity have been used for a variety of RNA sequencing (RNA-seq) applications, including comprehensive profiling of whole-cell, exosomal, and human plasma RNAs; quantitative tRNA-seq based on the ability of TGIRT enzymes to give full-length reads of tRNAs and other structured small ncRNAs; high-throughput mapping of post-transcriptional modifications; and RNA structure mapping. Here, we improved TGIRT-seq methods for compr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 54 publications
(100 reference statements)
4
74
0
Order By: Relevance
“…Under these conditions, we found larger differences in the amplitude of the reaction for acceptors with different 3' nucleotides in order G>C≈A>U ( Fig. 8A), which match the previously determined nucleotide sequence biases for TGIRT-seq (49). Additionally, when the reactions were carried out with lower concentrations of acceptor RNAs (10 nM) to more closely resemble the conditions during TGIRT-seq, the difference in amplitude for template switching to the most and least favored 3' nucleotides (G and U, respectively) increased ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Under these conditions, we found larger differences in the amplitude of the reaction for acceptors with different 3' nucleotides in order G>C≈A>U ( Fig. 8A), which match the previously determined nucleotide sequence biases for TGIRT-seq (49). Additionally, when the reactions were carried out with lower concentrations of acceptor RNAs (10 nM) to more closely resemble the conditions during TGIRT-seq, the difference in amplitude for template switching to the most and least favored 3' nucleotides (G and U, respectively) increased ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…Nucleotide sequence biases in TGIRT-seq reflect the efficiency of template switching to different 3' nucleotides of acceptor RNAs at high salt concentration--Previous TGIRT-seq analysis of miRNA reference sets showed that 3'-sequence biases in TGIRT-seq are almost completely confined to the 3'-terminal nucleotide of the acceptor, with a marked preference for miR-NAs with a 3' G residue and against those with a 3' U residue (49). In light of our finding that template switching is slower at high salt concentrations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, transcript chemistry, size and secondary structure will all introduce biases to the dataset ultimately used to draw the main conclusions. In addition, factors such as ligation biasthe preferential ligation of adapters to certain sequences (83,84), undoubtedly impacted the selection and ratios of the transcript ends we have reported. Therefore, our conclusionsparticularly quantitative onesshould be taken with those caveats in mind.…”
Section: The Chloroplast Tss Landscapementioning
confidence: 99%
“…12 ). Other steps with potential bias include the synthesis of the RNA by in vitro transcription with T7 RNA polymerase, which is known to 'slip' on repeated sequences 20 ; similar slippage or biased termination of reverse transcriptases in the RTase step after chemical modification [32][33] ; the ligation of adapters onto the resulting cDNAs, which are known to have sequence biases 22,30,34 ; Illumina sequencing-by-synthesis of cDNAs used, which is also known to have sequence biases 29 ; or the bioinformatic workup of these sequencing data into inferred chemical modification profiles. 29,35 We first sought to test if the poly(A) SHAPE and DMS signatures were due to the many possible biases occurring any steps downstream of reverse transcription, by carrying out the simplest method of reading out the cDNA products, capillary electrophoresis with fluorescently labeled primers.…”
Section: Anomalous Poly(a) Chemical Mapping Signal Is Recovered With mentioning
confidence: 99%